2005
DOI: 10.1002/dev.20056
|View full text |Cite
|
Sign up to set email alerts
|

Visual cortical activity during tactile perception in the sighted and the visually deprived

Abstract: This article reviews studies demonstrating activity in visual cortex during tactile perception in sighted participants as well as in those who have experienced visual deprivation of varying duration. This field has been very active over the last few years, with the result that a number of exciting findings have emerged, but a unifying framework is still lacking. The first section of this article deals with investigations revealing that visual cortical activity is regularly associated with the neural processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
97
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 62 publications
10
97
2
2
Order By: Relevance
“…These findings suggest a tight coupling between the continuous tactile information specifying a rotating object and the corresponding dynamic representation of the rotating object. This correspondence between haptic and visual modalities is in line with Sathian and colleagues' proposed account of haptic-visual translation for mental rotation (Prather & Sathian, 2002;Prather et al, 2004;Sathian, 2005). Research explicating the neural mechanisms underlying this relationship is in an incipient stage.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings suggest a tight coupling between the continuous tactile information specifying a rotating object and the corresponding dynamic representation of the rotating object. This correspondence between haptic and visual modalities is in line with Sathian and colleagues' proposed account of haptic-visual translation for mental rotation (Prather & Sathian, 2002;Prather et al, 2004;Sathian, 2005). Research explicating the neural mechanisms underlying this relationship is in an incipient stage.…”
Section: Discussionsupporting
confidence: 82%
“…Recent support for this claim has come from functional neuroimaging studies, which have shown activation in visual-processing regions during visual mental rotation tasks (e.g., Cohen et al, 1996;Kosslyn et al, 1998;Wraga, Shephard, Church, Inati, & Kosslyn, 2005). Sathian and colleagues have hypothesized that the tactile feedback participants receive during active and passive haptic mental rotation tasks may be translated into visual format for mental rotation (Prather & Sathian, 2002;Prather et al, 2004;Sathian, 2005). In the present study, we explored this issue using a behavioral paradigm.…”
Section: Methodsmentioning
confidence: 89%
“…Increasing evidence suggests that occipital cortex, in addition to its visual functions, is implicated in processing information from other sensory modalities (Sathian 2005;Schroeder and Foxe 2005;Sur and Leamey 2001). For example, after prolonged visual deprivation, visual cortex is recruited in a compensatory manner to process both tactile and auditory information (Burton et al 2002;Gougoux et al 2004;Kujala et al 1995;Roder et al 2002;Sadato et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Blind individuals may compensate for the lack of sight by developing hypereffective nonvisual senses. Although tactile input activates the visual cortex in sighted individuals 20 , blinds activate their primary visual areas V1 and V2 during Braille reading as a compensatory cross-modal strategy. 4 Blind subjects develop auditory abilities beyond controls 21 , and the absolute pitch is more prevalent in blind musicians 22 .…”
Section: Discussionmentioning
confidence: 99%